Electronic Coupling Effects of 2D Material Heterostructures and Their Applications in Flexible Optoelectronic Devices - Cong, Yueyang (Simen Owen Academic Proceedings Series, 2026)
In the post-Moore era, flexible optoelectronic devices are rapidly advancing towards wearable and portable applications, placing higher demands on material optoelectronic performance and mechanical flexibility. Single 2D materials have inherent limitations, graphene lacks a bandgap, limiting photoelectric conversion efficiency; transition metal dichalcogenides (TMDs) like MoS₂ have low carrier mobility; and black phosphorus is prone to oxidation, affecting long-term stability. These challenges are difficult to address through single material modification. 2D material heterostructures, formed through interlayer composite structures, leverage electronic coupling effects to enhance performance synergistically, providing an effective solution to overcome these limitations. This paper reviews common construction methods for typical 2D heterostructures, such as graphene-based, TMDs-based, and black phosphorus-based structures, including van der Waals stacking, covalent bonding, and solution assembly. It focuses on the mechanisms of interlayer charge transfer, exciton transfer, and orbital hybridization, and discusses how layer number control, strain application, and interface modification influence these coupling effects. Additionally, this work surveys the application of these heterostructures in flexible photodetectors, flexible light-emitting diodes (LEDs), and flexible solar cells, comparing their photoelectric response speed, energy conversion efficiency, and bending stability. Finally, challenges such as interlayer delamination, environmental instability, and difficulties in large-scale fabrication are discussed, with future directions in interface engineering and multifunctional heterostructure integration proposed for enhancing practical applications.